The first Chief Justice : John Jay and the struggle of a new nation - Dillon, Mark C. (Albany : State University of New York Press, 2022)
"Chronicles the efforts of the first Chief Justice of the US Supreme Court to establish a federal court system during the country's uncertain early years"--
Formative days in colonial New York -- Passing the rubicon : a key man in the birth of a nation -- Appointment as the Nation's first Chief Justice -- The Supreme Court's first argued case : West v. Barnes (1791) -- Grappling with the separation of powers : in re Hayburn (1792), plus ex parte Chandler and United States v Todd (unreported, 1794) -- Sovereign immunity and an impetus for the 11th Amendment : Chisholm v Georgia (1793) -- Resisting political pressure from the executive branch : Pagan v Hooper (1793) -- The Supreme Court's only reported jury trial and the supremacy of special jurors : the three appeals of Georgia v Brailsford (1792, 1793, and 1794) -- Trouble on the high seas : Glass v Sloop Betsey (1794) -- Efforts to criminally prosecute Chief Justice Jay : the citizen Genet affair -- Jay Court decisions of lesser note : Kingsley v Jenkins (1793), ex parte Martin (1793), and U.S. v Hopkins (1794) -- A final missionwhile Chief Justice -- After the Supreme Court -- History's verdict.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 04, 2022).
In English.
JSTOR
Keywords: Jay, John, -- 1745-1829.; United States. -- Supreme Court -- History; United States. -- Supreme Court -- Cases -- History; United States. -- Supreme Court -- Officials and employees -- Biography; États-Unis. -- Supreme Court -- Histoire; États-Unis. -- Supreme Court -- Jurisprudence -- Histoire; États-Unis. -- Supreme Court -- Fonctionnaires -- Biographies; Jay, John, -- 1745-1829; United States. -- Supreme Court; Judges -- United States -- Biography; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1809.; New York (State) -- Politics and government -- To 1775.; Juges -- États-Unis -- Biographies; États-Unis -- Politique et gouvernement -- 1775-1783.; États-Unis -- Politique et gouvernement -- 1783-1809.; New York (État) -- Politique et gouvernement -- Jusqu'à 1775.; HISTORY / United States / Revolutionary Period (1775-1800).; Employees; Judges; Politics and government; New York (State); United States; To 1809; Biographies; History; Trials, litigation, etc